2015
DOI: 10.1007/978-3-319-15856-3_13
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Embryo Presence and Viability

Abstract: Pregnancy establishment, followed by birth of live offspring, is essential to all mammals. The biological processes leading up to pregnancy establishment, maintenance, and birth are complex and dependent on the coordinated timing of a series of events at the molecular, cellular, and physiological level. The ability to ovulate a competent oocyte, which is capable of undergoing fertilization, is only the initial step in achieving a successful pregnancy. Once fertilization has occurred and early embryonic develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 109 publications
0
25
0
Order By: Relevance
“…Accurate positive pregnancy diagnosis varied between 60 and 100% for milk progesterone, however detection of non-pregnant animals varied between 81 to 100% (Nebel et al, 1987;Sasser, 1987, Nebel, 1988. Longer luteal phases in some cows, cysts or persistent follicles may play a role in elevated progesterone concentrations during the pregnancy test period that yield false positive results (Pohler et al, 2015a). Some discrepancies exist in evaluating the effectiveness of progesterone testing with regards to embryo loss.…”
Section: Chemical Based Pregnancy Testsmentioning
confidence: 99%
See 4 more Smart Citations
“…Accurate positive pregnancy diagnosis varied between 60 and 100% for milk progesterone, however detection of non-pregnant animals varied between 81 to 100% (Nebel et al, 1987;Sasser, 1987, Nebel, 1988. Longer luteal phases in some cows, cysts or persistent follicles may play a role in elevated progesterone concentrations during the pregnancy test period that yield false positive results (Pohler et al, 2015a). Some discrepancies exist in evaluating the effectiveness of progesterone testing with regards to embryo loss.…”
Section: Chemical Based Pregnancy Testsmentioning
confidence: 99%
“…They concluded that a IFNT-stimulated gene based pregnancy test would be possible for heifers at day 18 but not for cows whose response is more limited based on the current sensitivity of available assays (Green et al, 2010). Unfortunately, ISGs are not unique to pregnancy which limits their use as a pregnancy detection tool to identifying nonpregnant animals (Han et al, 2006;Gifford et al, 2007;Pohler et al, 2015a); however, a resynchronization protocol can be implemented in cows that are identified as non-pregnant which improves operation efficiency (Lucy et al, 2011).…”
Section: Chemical Based Pregnancy Testsmentioning
confidence: 99%
See 3 more Smart Citations